2011
DOI: 10.1007/s00339-011-6411-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the polymer emission on the electroluminescence characteristics of n-ZnO nanorods/p-polymer hybrid light emitting diode

Abstract: Hybrid light emitting diodes (LEDs) based on zinc oxide (ZnO) nanorods and polymers (single and blended) are fabricated and characterized. The ZnO nanorods were grown by the chemical bath deposition method at 50 o C. Three different LEDs, either with blue emitting, orange-red emitting or their blended polymer together with ZnO nanorods were fabricated and studied. The current-voltage characteristics show good diode behavior with ideality factor in the range of 2.1 to 2.27 for all the three devices. The electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The total injection barrier for the holes is therefore around 1.6 eV, and a large step is then made by the holes to reach the PFO/ZnO interface (band offset $1.8 eV), resulting in a total injection barrier of 3.4 eV for the carriers in this structure. 16 This value is in good agreement with the turn-on voltage mentioned above. The I-V characteristics of the LEDs fabricated with various PFO concentrations are shown in Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The total injection barrier for the holes is therefore around 1.6 eV, and a large step is then made by the holes to reach the PFO/ZnO interface (band offset $1.8 eV), resulting in a total injection barrier of 3.4 eV for the carriers in this structure. 16 This value is in good agreement with the turn-on voltage mentioned above. The I-V characteristics of the LEDs fabricated with various PFO concentrations are shown in Fig.…”
Section: Resultssupporting
confidence: 80%
“…However, the effects of the polymer thickness and of the variation of the injected current on the electrical and emission properties of PFO/ZnO NR-based hybrid LEDs were not investigated. 15,16 In this paper, we report on the effects of the PFO concentration on the overall performance of a hybrid white light emitting diode fabricated using ZnO NRs grown at 50 C on PFO/PEDOT:PSS multilayered polymers on flexible plastic substrates. Large electro-optical performance variations were found when varying the PFO concentration from 2 mg/ml up to 20 mg/ml.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer embedded nanostructures have eminent use for a number of technological applications, especially as advanced functional materials, viz., high-energy radiation shielding materials, microwave absorbers, optical filters, reflectors, optical limiters, polarizers, and sensors. Thus, the incorporation of inorganic NPs in the polymer system significantly increases the physical parameter range beyond that of the host polymer and allows the material properties for the explicit applications. In particular, the optical properties of polymer nanocomposite (NC) films have huge interest for optoelectronics and photonics devices. The properties of polymer NC films depend on the size, shape, and concentration of incorporated NPs and their interaction with the polymer films. Incorporation of NPs inside the polymer system provides flexibility and stability. Additionally, polymer encapsulation systems help in preventing both oxidation and aggregation of NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Decrease in overall EL and device stability was observed for the above configuration which is contradictory to the previous work reported by Asbahi et al [7] where the enhancement in green emission was observed on incorporating TiO 2 nano-particles in the emissive layer of PFO. It has already been demonstrated that polyfluorene photodegrades in the presence of oxygen [10,12] and so quenching of luminescence was observed using TiO 2 -PFO nanocomposite. with the same device configuration as for device 1.…”
Section: Resultsmentioning
confidence: 97%